TRAINING IN CREATING INTERACTIVE LEARNING MEDIA USING THE CANVA APPLICATION FOR FACULTY OF TEACHER TRAINING AND EDUCATION’S STUDENTS AT ABULYATAMA UNIVERSITY - Dewi, Shinta; Anzora, Anzora; Susiani, Rini; Dauyah, Ema; Suryani, Suryani (Universitas Muhammadiyah Aceh, 2024)
Learning media plays an important in learning. Through interactive learning media, students can achieve a deeper understanding of the material.. Matematics Education students know that they will kmprove their skills in creating learning media to improve the quality of learning and they request training in creating learning media.there are several application that can be utilised, including Canva. Canva has many menu services to create interactive learning materials. Therefore this service aims to provide learning media. SThe working method is a training method where participants practice directly on Canva. The result of this activity is that students can design interactive learning media using Canva. Based on the evaluation results of this activity, the training was successful.Keywords:Interactive Learning Media, Canva, Student